Highlights from the HIV Cure and Reservoir Symposium, 11-12 September 2017, Ghent, Belgium - Sam Kint; Clarissa Van Hecke; Basiel Cole; Linos Vandekerckhove; Magdalena Sips (Elsevier, 2018)
For the second time, the HIV Cure Research Center (HCRC) at Ghent University organised the HIV Cure and Reservoir Symposium, in Ghent, Belgium, where in this two-day conference, virologists, molecular biologists, immunologists and clinicians presented the most recent achievements in the field of HIV cure, including data on therapeutic vaccines, HIV remission strategies such as 'shock and kill' or 'block and lock', benefits of early ART and potential of haematopoietic stem cell transplant in achieving cure. Furthermore, methods to characterise and quantify the HIV reservoir were discussed along with HIV reservoir characterisation in different body parts, including the central nervous system. An HIV activist and representative of a patients' agency also presented the patients' perspective on HIV cure. This report is a summary of all topics discussed during this symposium.